PENGARUH PEMBERIAN MESENCHYMAL STEM CELL WHARTON’S JELLY TERHADAP KADAR GLUKOSA DARAH PADA TIKUS WISTAR (RATTUS NORVEGICUS) HIPERGLIKEMIA - Magza, Dekasih Tria; Endrinaldi, Endrinaldi; Afriani, Nita; Arisanty, Dessy; Welan, Rahmani; Rustam, Erlina (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Diabetes mellitus (DM) is a metabolic disease characterized by blood glucose levels above normal or hyperglycemia caused by defects in insulin secretion, insulin action, or both. This study aims to determine the effect of wharton’s jelly mesenchymal stem cells on blood glucose levels in hyperglycemic Wistar rats (Rattus norvegicus). This research is a laboratory experimental study using a post-test control group design. This research was conducted on 18 male white rats (Rattus norvegicus) which were divided into 3 groups, namely the normal/negative group (K-), the positive control group (K+) which was induced by alloxan, and the three treatment groups (P) which were induced by alloxan, alloxan and given a single dose of 3x106 cells of Wharton’s jelly mesenchymal stem cells for one month. Blood glucose levels were measured using a glucometer every week, from the first week to the 5th week. Data analysis used the Kruskal-Wallis and Mann-Whitney tests. Mean of blood glucose level in the last week with a glucometer in the (P) group was 85.33 mg/dL, lower than that in the (K+) group, namely 551.5 mg/dL. However, the (K-) group was the lowest compared to the (P) and (K+) groups, namely 72.83 mg/dL The data showed that there was a significant difference in blood glucose levels between groups (p<0.05). The conclusion of the study was that the administration of Wharton’s jelly mesenchymal stem cells had an effect on reducing blood glucose levels in hyperglycemic rats